Philodryas agassizi (jan, 1863) (squamata: Dipsadidae): Distribution extension - Perez, Cristian Hernan Fulvio (2012)
We provide the first record of Philodryas agassizi from Río Negro province, as well as the southernmost record from La Pampa Province, central Argentina. The record from Río Negro province extends the geographic distribution range of this species by approximately 180 km south.